Cognitive Benefits From a Musical Activity in Older Adults - Diaz Abrahan, Veronika; Shifres, Favio; Justel, Nadia (Frontiers in Psychology, 2019)
The aging population is growing rapidly. Proposing interventions that enhance the cognitive reserve or strategies that delay the onset of disabilities associated with age is a topic of capital interest for the biopsychosocial health of our species. In this work, we employed musical improvisation as a focal environmental activity to explore its ability to improve memory in older adults. We present two studies: the first one evaluated neutral memory using the Rey Complex Figure (RCF) and the second one evaluated emotional memory using International Affective Picture System (IAPS). A group of 132 volunteers, between the ages of 60 and 90, participated in this investigation. Fifty-one of them were musicians with more than five years of formal musical training. After acquisition of neutral (study 1) or emotional (study 2) information, the groups of older adults were exposed to music improvisation (experimental intervention) or music imitation (control intervention) for three minutes. We then evaluated memory through two tasks (free recall and recognition), by means of immediate and deferred measures (after a week). We found a significant improvement in memory among participants involved in music improvisation, who remembered more items of the RCF and images from IAPS than the imitation group, both in the immediate and deferred evaluation. On the other hand, subjects who had musical knowledge had a better performance in neutral visual memory than non-musicians. Our results suggest that a focal musical activity can be a useful intervention in older adults to promote cognitive skills and prevent cognitive impairment.